Tick bites in different professions and regions: pooled cross-sectional study in the focus area Bavaria, Germany - Louisa Schielein; Linda Tizek; Tilo Biedermann; Alexander Zink (BMC, 2022)
Abstract Background As the vector-borne diseases tick-borne encephalitis (TBE) and Lyme borreliosis (LB) are common in Germany and transmitted by tick bites, the aim of this study was to assess differences in the number of tick bites in various professions and regions across southern Germany to evaluate the differences in tick-associated risk. Materials and methods The analysis is based on three cross-sectional studies that were conducted in 2016 and 2017 in two real-life settings and in one medical setting in Bavaria. All participants filled in a paper-based questionnaire about their history with tick bites. Only adult participants (≥ 18 years) were included in this study. Results Overall, 3503 individuals (mean age 50.8 ± 15.2 years, median age 53.0 ± 12.2 years, 54.0% female) were included. Of these, 50% worked in an outdoor profession and 56% lived in environs. Around 70% of participants reported at least one previous tick bite. In comparison to indoor workers, forestry workers (OR = 2.50; 95% CI: 1.10-5.68) had the highest risk for a tick bite followed by farmers (OR = 1.22; 95% CI: 1.01-1.47). Furthermore, people living in rural areas (OR = 1.97, 95% CI:1.49-2.59) and environs (OR = 1.98, 95% CI: 1.54-2.55) were twice as likely to have a previous tick bite than people living in urban areas. In general, slightly more tick bites were reported by people living in eastern Bavaria. Conclusion Rising numbers of TBE and LB indicate the need for further prevention strategies, which should focus on outdoor professions with a higher risk and people living in environs and rural areas.